2008
DOI: 10.1103/physrevb.77.075403
|View full text |Cite
|
Sign up to set email alerts
|

Energy-gap modulation of BN ribbons by transverse electric fields: First-principles calculations

Abstract: Systematic ab initio calculations show that the energy gap of boron nitride (BN) nanoribbons (BNNRs) with zigzag or armchair edges can be significantly reduced by a transverse electric field and completely closed at a critical field which decreases with increasing ribbon width. In addition, a distinct gap modulation in the ribbons with zigzag edges is presented when a reversed electric field is applied. In a weak field, the gap reduction of the BNNRs with zigzag edges originates from the field-induced energy l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
197
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 281 publications
(216 citation statements)
references
References 31 publications
17
197
1
1
Order By: Relevance
“…A relevant electronic property for purposes of optical applications and quantum confinement effect is related to the scaling behaviour of the band gap with ribbon width, as previously investigated in the literature for 2D materials, for instance: graphene nanoribbons 1,2,29-31,41,42 , boron nitride nanoribbons 43,44 , silicene nanoribbons [45][46][47][48] and phosphorene nanoribbons 23,32,33 . Recent studies via first principles calculations have indicated that the band gaps of BPNs possess different scaling laws depending on the edge type and thus suggesting its usage as a convenient tool for identifying acBPNs and zzBPNs samples with similar geometric widths, since the previous results have shown that the band gap is larger in zzBPNs than in acBPNs for the same ribbon width.…”
Section: Scaling Laws Of Band Gaps For Phosphorene Nanoribbonsmentioning
confidence: 99%
“…A relevant electronic property for purposes of optical applications and quantum confinement effect is related to the scaling behaviour of the band gap with ribbon width, as previously investigated in the literature for 2D materials, for instance: graphene nanoribbons 1,2,29-31,41,42 , boron nitride nanoribbons 43,44 , silicene nanoribbons [45][46][47][48] and phosphorene nanoribbons 23,32,33 . Recent studies via first principles calculations have indicated that the band gaps of BPNs possess different scaling laws depending on the edge type and thus suggesting its usage as a convenient tool for identifying acBPNs and zzBPNs samples with similar geometric widths, since the previous results have shown that the band gap is larger in zzBPNs than in acBPNs for the same ribbon width.…”
Section: Scaling Laws Of Band Gaps For Phosphorene Nanoribbonsmentioning
confidence: 99%
“…[29][30][31] Though BN has the same planar structure as graphene due to the ionic character of B-N bonds, BN crystal is a wide band gap insulator with an energy gap of 4.6 eV. [32][33][34][35] The perfect lattice matching between graphene and BN layers make it possible to construct nanoscale devices. 36 Following the synthesis of hexagonal monolayer of ZnO, 37 the II-VI metal-oxide analogue of graphene, it was also predicted that ZnO nanoribbons have ferromagnetic order in their ground state.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of their structural similarities, the two materials are completely distinct electrically: graphene is a good conductor and h-BN is a good insulator [3][4][5][6] . Recently, several attempts have been made to build graphene devices on h-BN substrates to exploit their complementary properties [7][8][9][10] .…”
mentioning
confidence: 99%